KESANTUNAN BERBAHASA MELAYU SAMBAS DI LINGKUNGAN KELUARGA MASYARAKAT DESA SEBURING - Safhira, Bela; Sulissusiawan, Ahadi; Simanjuntak, Hotma (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study focuses on the use of politeness in the Sambas Malay community within the family sphere in Seburing Village. The main objective is to describe the forms of politeness used in family interactions and to uncover the factors that influence their use. The approach used is qualitative with descriptive methods. Data were obtained through observation and recording techniques. The results of the study indicate that the Sambas Malay community in Seburing Village still maintains the principles of politeness in language, especially in communication between children and parents, as well as between siblings. This politeness is reflected through word choice, use of greetings, intonation, and speaking strategies that emphasize respect. Factors determining the use of polite language include cultural background, religious values, and prevailing social norms. These findings indicate that politeness plays an important role in maintaining harmonious family relationships and is a cultural identity of the Sambas Malay community.